PENGARUH PENDEKATAN CONTEXTUAL TEACHING AND LEARNING UNTUK MENGEMBANGKAN KEMAMPUAN BERBAHASA ANAK USIA DINI 5-6 TAHUN: THE EFFECT OF THE CONTEXTUAL TEACHING AND LEARNING APPROACH ON DEVELOPING LANGUAGE SKILLS IN CHILDREN AGED 5–6 YEARS - Intisari; Purwanti, Duwi (Universitas Islam Malang, 2024)
Children's language skills at an early age are the foundation that needs to be trained to express their ideas and thoughts, including the ability to read and write. This research aims to determine contextual teaching and learning on the language skills of young children aged 5-6 years at Pelangi Bulukumba Kindergarten. Data collection in this study used observation techniques with research subjects consisting of 24 children from class B1 and 20 children from class B2. To obtain research results, researchers used a quantitative approach with a quasi-experimental design with descriptive analysis techniques and comparative tests using the independent samples t-test. The research results show that the language skills of students who took part in experimental activities, with a mean value of 19.40, showed a significant increase compared to the control class which had a mean value of 15.00. This proves that there is an influence of contextual teaching and learning on the language skills of young children aged 5-6 years at Pelangi Bulukumba Kindergarten.